A Review on Analgesic: From Natural Sources. - Zafar, Akbar (International Journal of Pharmaceutical & Biological Archive, 2010)
Analgesics are the painkiller substances, which act by the absence of pain without losing consciousness. The word analgesic derives from Greek an- ("without") and algos ("pain"). Analgesic drugs act in various ways on the peripheral and central nervous systems. There are various sources of analgesic drugs, some synthetic drugs like- Peracetamol, cox2 inhibitor, NSAIDs, Ibuprofen, diclofenac etc. Medicinal plants also the rich source of analgesics like as- Opoid analgesics, Aloevera Barbedensis, Andrographis Paniculata, Elettaria cardamomum, Punica granatum, Eugenia caryophyllus , mimosa, Curcuma alismatifolia, Phoenix sylvestris, Stachys schtscheglee, Cissus quadrangularis, menthol , Bunts longifolia, Buxus sempervirens, Burns sempervirens, Fumaira vaillantii, Rumex crispus, Urtica dioica, Morinda Citrifolia etc. This review gives an idea for analgesics which obtained from different natural sources.